1959
DOI: 10.3109/00365515909060432
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Dehydrogenase Activity in Pleural and Peritoneal Effusions

Abstract: Scand J Clin Lab Invest Downloaded from informahealthcare.com by University of Alberta on 12/12/14For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…23 In our study, simultaneous use of these three tests failed to perform as well as in Light's study ( Table 2). The compartmentalised elevation of LDH concentration in the exudative processes may explain why the LDHr has no role in the diagnostic separation of PE into transudate and exudate, 29,35 and why when this parameter is used to separate an exudate from a transudate the sensitivity decreases, as also showed in more recent humans studies. 3e5 Although RBCs contain a large amount of LDH, one human study demonstrated no correlation between the pleural fluid LDH level and pleural fluid RBC, 2 while another supported a relationship between RBC and LDH.…”
Section: Discussionmentioning
confidence: 87%
“…23 In our study, simultaneous use of these three tests failed to perform as well as in Light's study ( Table 2). The compartmentalised elevation of LDH concentration in the exudative processes may explain why the LDHr has no role in the diagnostic separation of PE into transudate and exudate, 29,35 and why when this parameter is used to separate an exudate from a transudate the sensitivity decreases, as also showed in more recent humans studies. 3e5 Although RBCs contain a large amount of LDH, one human study demonstrated no correlation between the pleural fluid LDH level and pleural fluid RBC, 2 while another supported a relationship between RBC and LDH.…”
Section: Discussionmentioning
confidence: 87%
“…But the benign effusions in all 4 series were mainly transudates. Kirkeby and Prydz (18) first suggested that elevated pleural-fluid LDH may be characteristic of all inflammatory . .…”
Section: Discussionmentioning
confidence: 99%
“…This results in the questionable adoption of the same cut-off value for different species (ie, dogs and cats) and for a different anatomical localisation of the effusion (ie, pleural and abdominal effusions). 14 A recent study of 20 cats demonstrated that Light's criteria, with cut-off points for its parameters adapted to the feline species (Table 1), allowed, as in human medicine, 1,[3][4][5][6]15,16 the discrimination of the pathophysiology of pleural effusion (ie, transudates vs exudates) with an accuracy ⩾90%. 17 Using the traditional veterinary classification on the same 20 cats, [12][13][14] the overall accuracy in discriminating the pathophysiological origin of the effusion was only 40%.…”
Section: Introductionmentioning
confidence: 99%